Supreme justice : a novel of suspense - Margolin, Phillip (Harper, 2010)
Attorney Brad Miller, FBI agent Keith Evans, and private investigator Dana Cutler untangle a five-year-old murder case involving a ghost ship and the President's nominee to the U.S. Supreme Court.